The divergent outcome of IL-4Rα signalling on Foxp3 T regulatory cells in listeriosis and tuberculosis - Chia, Julius E.; Rousseau, Robert P.; Ozturk, Mumin; Poswayo, Sibongiseni K. L.; Lucas, Rodney; Brombacher, Frank; Parihar, Suraj P. (Frontiers in Immunology, 2024)
Forkhead box P3 (Foxp3) T regulatory cells are critical in the maintenance of self-tolerance, immune homeostasis and regulation of the immune system. We investigated interleukin-4 receptor alpha (IL-4Rα) signalling on T regulatory cells (Tregs) in Listeria monocytogenes (Lm) infection using a mouse model in BALB/c background with IL-4Rα specifically knockdown on Tregs (Foxp3 cre IL-4Rα -/lox ). We showed an impairment of Treg responses, with a decreased bacterial burden and diminished tissue pathology in the liver and spleen, which translated into better survival. Mechanistically, we observed enhancement of Th1 signature with the characteristic T-bet transcriptional factor expression and increased effector T cells producing IFN-γ, IL-2 following ex-vivo stimulation with heat-killed Lm in Foxp3 cre IL-4Rα -/lox mice. Furthermore, CD8 T cells from Foxp3 cre IL-4Rα -/lox mice displayed increased cytotoxicity (Granzyme-B) with higher proliferation capacity (Ki-67), better survival (Bcl-2) with concomitant reduced apoptosis (activated caspase 3). In contrast to Lm, Foxp3 cre IL-4Rα -/lox mice displayed similar bacterial burdens, lung pathology and survival, despite increased T cell numbers and IFN-γ, TNF and IL-17 production during Mycobacterium tuberculosis (Mtb) infection. Our results demonstrated that the loss of IL-4Rα signalling on Foxp3 + T regulatory cells resulted in their functionality loss, which in turn led to survival benefit in listeriosis but not in tuberculosis. of Health under Award Number K43TW012587. The content is solely the responsibility of the authors and does not necessarily represent the views of the funders. The research was conducted in the BSL3 equipment platform supported by core funding from the Wellcome Trust (203135/Z/16/Z). For the purpose of open access, the author has applied a CC BY public copyright license to any Author Accepted Manuscript version arising from this submission.